DNA EVIDENCE, NEW TECHNOLOGIES AND JUSTICE’S APPLICATIONS: AN INTERNATIONAL COMPARATIVE OVERVIEW - D'Orio, Eugenio; Lucanto, Chiara; Francione, Gennaro (International Journal of Law in Changing World, 2022)
Modern technologies represent an increasingly useful tool in the justice system, and their direct application affects practically every single branch of justice, from the civil trial, to the criminal trial, to the computerised organisation of judgments and their availability to legal practitioners, to applications of artificial intelligence (AI). In the field of criminal trials, DNA examination technologies represent an important tool for acquiring scientific information that is increasingly useful for a proper search for historical truth. These technologies, which are constantly evolving, have characterised trials and investigations all over the world since the early 2000s. However, this technical evolution is often not followed by a regulatory evolution, the purpose of which would be to assist and maximise the use of these new technologies in the justice system. This article will highlight, in a comparative manner, the current European and extra-European laws on the regulation of genetic evidence. An in-depth focus will be made both on regulatory aspects both on aspects related to the new scientific methodologies and how their use can affects human rights, with particular regard to the protection of citizens' basilar human rights.